(untitled) (Global Journal of Medical Research, 2019)
As the most voluminous organ of the body that is exposed to the outer environment, the skin suffers from both intrinsic and extrinsic aging factors. Skin aging is characterized by features such as wrinkling, loss of elasticity, laxity, and rough-textured appearance. This aging process is accompanied with phenotypic changes in cutaneous cells as well as structural and functional changes in extracellular matrix components such as collagens and elastin. With intrinsic aging, structural changes occur in the skin as a natural consequence of the biological changes over time and produce a certain number of histological, physiological, and biochemical modifications. Intrinsic aging is determined genetically (influence of gender and ethnic group), variable in function of skin site, and also influenced by hormonal changes. Visually it is characterized by fine wrinkles. By comparison, "photoaging" is the term used to describe the changes occurring in the skin, resulting from repetitive exposure to sunlight. The histological, physiological, and biochemical changes in the different layers of the skin are much more drastic. From a mechanical point of view, human skin appears as a layered composite containing the stiff thin cover layer presented by the stratum corneum, below which are the more compliant layers of viable epidermis and dermis and further below the much more compliant adjacent layer of subcutaneous white adipose tissue.